In vitro study of the Polo‐like kinase 1 inhibitor volasertib in non‐small‐cell lung cancer reveals a role for the tumor suppressor p53. Issue 5 (5th April 2019) - Van den Bossche, Jolien; Deben, Christophe; De Pauw, Ines; Lambrechts, Hilde; Hermans, Christophe; Deschoolmeester, Vanessa; Jacobs, Julie; Specenier, Pol; Pauwels, Patrick; Vermorken, Jan Baptist; Peeters, Marc; Lardon, Filip; et al.
Abstract : Polo‐like kinase 1 (Plk1), a master regulator of mitosis and the DNA damage response, is considered to be an intriguing target in the research field of mitotic intervention. The observation that Plk1 is overexpressed in multiple human malignancies, including non‐small‐cell lung cancer (NSCLC), gave rise to the development of several small‐molecule inhibitors. Volasertib, presently the most extensively studied Plk1 inhibitor, has been validated to efficiently reduce tumor growth in preclinical settings. Unfortunately, only modest antitumor activity against solid tumors was reported in clinical trials. This discrepancy prompted research into the identification of predictive biomarkers. In this study, we investigated the therapeutic effect of volasertib monotherapy (i.e., cytotoxicity, cell cycle distribution, apoptotic cell death, cellular senescence, and migration) in a panel of NSCLC cell lines differing in p53 status under both normal and reduced oxygen tension (<0.1% O2 ). A strong growth inhibitory effect was observed in p53 wild‐type cells (A549 and A549‐NTC), with IC50 values significantly lower than those in p53 knockdown/mutant cells (A549‐920 and NCI‐H1975) ( P < 0.001). While mitotic arrest was significantly greater in cells with nonfunctional p53 ( P < 0.005), apoptotic cell death ( P < 0.026) and cellular senescence ( P < 0.021) were predominantly induced in p53 wild‐type cells. Overall, the therapeutic effect of volasertib was reduced under hypoxia ( P < 0.050). Remarkably, volasertib inhibited cell migration in all cell lines tested ( P < 0.040), with the exception of for the NCI‐H1975 p53 mutant cell line. In conclusion, our results show an important difference in the therapeutic effect of Plk1 inhibition in NSCLC cells with versus without functional p53. Overall, the p53 wild‐type cell lines were more sensitive to volasertib treatment, suggesting that p53 might be a predictive biomarker for Plk1 inhibition in NSCLC. Moreover, our results pave the way for new combination strategies with Plk1 inhibitors to enhance antitumor activity. Abstract : Polo‐like kinase 1 (Plk1), a regulator of mitosis, is overexpressed in human malignancies, making it an intriguing target. However, only modest antitumor activity against solid tumors was reported in clinical trials investigating the Plk1 inhibitor volasertib. We demonstrate that p53 might be a predictive biomarker for Plk1 inhibition in NSCLC. Moreover, our results pave the way for new combination strategies.